Multi-Disciplinary Digital Signal Processing A Functional Approach Using Matlab - Gopi, E. S. (Springer International Publishing, 2018)
This book provides a comprehensive overview of digital signal processing for a multi-disciplinary audience. It posits that though the theory involved in digital signal processing stems from electrical, electronics, communication, and control engineering, the topic has use in other disciplinary areas like chemical, mechanical, civil, computer science, and management. This book is written about digital signal processing in such a way that it is suitable for a wide ranging audience. Readers should be able to get a grasp of the field, understand the concepts easily, and apply as needed in their own fields. It covers sampling and reconstruction of signals; infinite impulse response filter; finite impulse response filter; multi rate signal processing; statistical signal processing; and applications in multidisciplinary domains. The book takes a functional approach and all techniques are illustrated using Matlab. Presents a multi-disciplinary approach to digital signal processing; Written using a functional approach with all techniques illustrated using Matlab; Pertinent to research scholars, electrical, electronics, computer science, mechanical, civil, and chemical engineers. .